An An Overview of Mathematics Laboratory in School Level Education in Nepal - Kunwar, Rajendra (Rupantaran: A Multidisciplinary Journal, 2023)
The article explores the discourse of mathematics laboratories concerning classroom teaching. It focuses on the mathematics teachers' knowledge and awareness about the use of mathematics laboratories and their importance, especially in school-level education in Nepal. The study is descriptive in nature. It is chiefly based on the review of previous literature. This article presents a short glimpse into mathematics education, teaching mathematics, and an outline of mathematics laboratories precisely. It also discusses the different aspects of the mathematics laboratory. The mutual support for transforming knowledge through classroom practice in teaching and learning mathematics to overcome the constraints has also been discussed. Also, it provides ways of sharing experiences by working together with the use of varied modern tools and technology in the classroom practice that helps to encourage the students to take part in the learning process actively and make them clear different mathematical concepts as well. It also suggests the establishment and utilization of a mathematics laboratory for the concerned mathematics teachers and administrators of the school to facilitate and conduct effective mathematics teaching.